1970
DOI: 10.3329/jbt.v5i2.9986
|View full text |Cite
|
Sign up to set email alerts
|

Online Marketing in Bangladesh: A Descriptive Study in the Context of Some Selected Click and Mortar Businesses

Abstract: Every business requires a good marketing mix to introduce, grow, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…It is found that the attitude towards online communication is different from the attitude of consumers towards traditional communication. Hassan et al (2010) suggest that entertainment, information seeking, value creation, credibility, and usefulness for the economy are the primary antecedents of attitude in approaching online communication. The relationships among the constituent antecedents such as information and entertainment are perceptual while a strategic coherence between online and traditional media is necessary for a comprehensive IMC program (Foroudi et al, 2017).…”
Section: Online Marketing Communication and Higher Education Brandingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the attitude towards online communication is different from the attitude of consumers towards traditional communication. Hassan et al (2010) suggest that entertainment, information seeking, value creation, credibility, and usefulness for the economy are the primary antecedents of attitude in approaching online communication. The relationships among the constituent antecedents such as information and entertainment are perceptual while a strategic coherence between online and traditional media is necessary for a comprehensive IMC program (Foroudi et al, 2017).…”
Section: Online Marketing Communication and Higher Education Brandingmentioning
confidence: 99%
“…The "search engine" is a very useful tool mainly to drive specific customers to specific brands of choice. For instance, Hassan (2010) observed that more than eighty percent online surfers use it as their primary medium to search for information.…”
Section: Gkmc 693mentioning
confidence: 99%
“…On the contrary, insecure electronic payments, slow transmission lines, a lack of affordable merchandise demonstrations, and the technical inability to bring friends along on a shopping trip are all technology-based impediments to consumer acceptance (Jarvenpaa et al, 2000). However, the case of Bangladesh is intriguing because, while online shopping has grown in popularity over the years, the use of technology for digital marketing has become increasingly complicated (Hassan et al, 1970; Rahman et al, 2018). This research may unfold something exciting and novel to alleviate pressing issues and pave the way for a more convenient online shopping experience.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true in India and Bangladesh. Compared to Bangladesh, India was quicker to embrace fashion (Hassan et al, 2010). In addition to wellknown companies like Amazon and eBay, they operate other websites devoted to products like apparel, home furnishings, and cuisine.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hassan et al (2010) provide an inside look at the web marketing efforts of various Bangladeshi business marketers. This is a quantitative study that utilizes both secondary and primary data.…”
Section: Introductionmentioning
confidence: 99%